THE INFLUENCE OF VOCABULARY LEARNING STRATEGIES ON STUDENTS’ READING COMPREHENSION IN EFL CONTEXTS (SCIENCE TIME JOURNAL, 2026)
Vocabulary plays a vital role in the development of reading comprehension skills, especially in the context of learning English as a Foreign Language (EFL). Language learners who possess a broader and deeper vocabulary repertoire are generally able to process written texts with greater ease and accuracy. Thus, the acquisition of vocabulary is not only fundamental to linguistic development but is also critical to comprehending and interpreting a variety of reading materials. Vocabulary learning strategies (VLS) refer to the intentional, systematic methods and techniques that students employ to enhance their knowledge and retention of new words. The effectiveness of these strategies is now widely studied, and their influence on reading comprehension in EFL contexts has attracted significant scholarly attention.This study investigates the impact of vocabulary learning strategies on students’ reading comprehension using a quasi-experimental design. The results indicate that students who applied vocabulary learning strategies demonstrated significantly improved reading comprehension compared to those who did not.